Effect of Game-Based Learning in Vehicle Air-Conditioning Course on Cognitive and Affective Skills of Vocational Students - Azizan, Intan Diyana; Alias, Maizam; Mustafa, Mohamad Zaid (Journal of Technical Education and Training, 2021)
Refrigerant and air conditioning course in vocational college is challenging to students and teachers as indicated by the unsatisfactory student’s examination results. Students come diverse backgrounds with poor basic skills and low motivation which, is difficult to address using the traditional interactive teaching and learning methods as currently practiced by teachers Therefore, game-based learning is suggested as an alternative to increase students’ motivation and achievement. A study was conducted to assess the effect of game-based learning on learning of the cognitive (recall the fact, concept, and procedure) and affective (respond/reaction) skills of vocational students in automotive air-conditioning course. A quasi-experiment was conducted on 30 students from two vocational colleges who were randomly assigned to the experimental and control group. The experimental group underwent a game-based learning method and tested using pre-test, post-test, and questionnaire. Whereas the control group underwent the existing method and tested using only pre-test and post-test. The teaching and learning module were developed based on the ADDIE model. The module has been analysed for usability and method. The results of this experiment show that the achievement of the experimental group is better than the control group. The students show good responses and reactions towards game-based learning. In conclusion, game-based learning is effective for student’s cognitive and affective skills in this course.